Considering Bilingual Dictionaries Against a Corpus. Do English-French Dictionaries Present "Real English"? - Noël, Dirk; Defrancq, Bart; Devos, Filip (Lexikos, 1995)
This article investigates the extent to which four representatives of the latest generation of English-French / French-English dictionaries present "real English", i.e. actually used meanings of actually used English word patterns. The findings of a corpus study of the verb CONSIDER are confronted with the entries for this verb in the English-French sections of these dictionaries, leading to the conclusion that there are important gaps in both the semantics and the lexicogrammar they cover, and that the organization of entries does not match the corpus frequency data. Corpus research could help to fill the gaps and should therefore be taken seriously by compilers of bilingual dictionaries.